Visualizing harm reduction: Methodological and ethical considerations. (May 2015) - Switzer, S.; Guta, A.; de Prinse, K.; Chan Carusone, S.; Strike, C.
Abstract: The use of visual methods is becoming increasingly common and accepted in health research. This paper explores the opportunities and constraints of using photo-based methods in the context of a community-based participatory research study on how to engage people living with HIV in conversations about a hospital's recently introduced harm reduction policy. Using a blended approach of photovoice and photo-elicited interviews, we provided participants (n = 16) with cameras and asked them to take a series of photos that "show how you feel about or have experienced harm reduction as a Casey House client." We reflect on methodological insights from the study to think through the process of doing photo-based work on a stigmatized topic in a small hospital setting by foregrounding: 1) how the act of taking photos assisted participants in visualizing connections between space, harm reduction, and substance use; 2) expectations of participation and navigating daily health realities; and 3) issues of confidentiality, anonymity and stigma in clinical settings. These reflections provide a case study on the importance of critically examining the process of engaging with photo-based methods. We conclude the paper by re-thinking issues of context and photo-based methods. Rather than viewing context as a neutral backdrop to apply a method, context should be viewed as an active force in shaping what can or cannot be done or produced within the space. Photo-based methods may offer an effective community-engagement strategy but may require modification for use in a clinical setting when working on a stigmatized topic with individuals with complex health care needs. Given the potential of visual methods as a community engagement strategy, research teams are advised to understand the entire process as a data collection opportunity so that these methods can be further explored in a variety of contexts. Highlights: We explore opportunities and constraints of using photovoice in an HIV CBPR project. We consider how participants visualize space, harm reduction, and substance use. We explore issues of anonymity, confidentiality and stigma in clinical settings. We discuss the process of engaging with photo-based methods for data collection.